Health promoting schools: consensus, strategies, and potential. Issue 3 (2014) - ,; ,; ,
Abstract : Purpose – The purpose of this paper is to summarize a consensus statement generated on the current challenges, strategies, and potential of health promoting schools (HPS) at a 2011 colloquium at the Stellenbosch Institute for Advanced Study where 40 people from five continents came together to share their global and regional experience surrounding the World Health Organization (WHO) HPS model.Design/methodology/approach – Using the consensus as its foundation, this review summarizes the underlying educational and social science concepts and factors that contribute to success or failure of HPS, and incorporates peer reviewed papers based on invited presentations at the colloquium and key related literature.Findings – HPS increase knowledge and develop behaviors that benefit the health of children, such schools are also an investment in the well‐being of the larger community. Importantly for their long‐term psychological health "resilience" is generated by effective HPS programs. Professional development initiatives within schools can catalyze greater absorption of the healthy school approach and focus on best practices. Promotion, support, and evaluation of programs are aided by award schemes and oversight by local or national agencies. And significant educational benefits are accrued for trainees from centers of higher learning involved in HPS program delivery.Practical implications – Educational initiatives that utilize the relative simplicity, low cost, and inherent flexibility of the HPS model can address many significant issues facing today's children. HPS offer an innovative and participatory way to increase the likelihood of the next generation becoming aware of practical ways to positively influence their lifestyle and future well‐being. Successful programs are usually those that are relevant, resonate with students, and engage school communities so that they choose to "own" and sustain their program.Originality/value – The consensus statement provides a benchmark of the current status of HPS, and outlines future directions for this model of health promotion. Acknowledgements : The authors wish to acknowledge support from the "International Colloquium Abroad" program of the Peter Wall Institute for Advanced Studies (PWIAS), University of British Columbia, Canada and the "Visiting Research Fellow" program of the Stellenbosch Institute for Advanced Studies (STIAS), Stellenbosch University, South Africa. Also provision of the conference facilities at the Wallenberg Research Centre by STIAS.